2019
DOI: 10.1136/thoraxjnl-2018-212709
|View full text |Cite
|
Sign up to set email alerts
|

Change in type-2 biomarkers and related cytokines with prednisolone in uncontrolled severe oral corticosteroid dependent asthmatics: an interventional open-label study

Abstract: Type-2 biomarkers and related cytokines (IL-5, IL-13), lung function and asthma symptoms were measured in 44 poorly-controlled severe oral corticosteroid (OCS)-dependent asthmatics for up to 88 days after a 7-day prednisolone boost (0.5 mg/kg). High-dose OCS reduced median blood eosinophils (−60 cells/µl; 95% CI −140 to 10), periostin (−8.4 ng/mL; −11.6 to –2.8), FeNO (−19.0 ppb; −28.5 to –4.0), IL-5 (−0.17 pg/mL; −0.28 to –0.08) and IL-13 (−0.15 pg/mL; −0.27 to –0.03). There were small improvements in mean FE… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(13 citation statements)
references
References 10 publications
0
13
0
Order By: Relevance
“…The smallest reduction of 41% (95% CI: 15, 66) was observed in a study where all patients were receiving at least 10mg of maintenance OCS daily. [18] Sputum eosinophils were reduced by 89% (95% CI: 79, 98; Figure 3), with decreases of in excess of 80% reported in eight (80%) studies. Mean sputum eosinophils were less than 3% in nine (90%) studies following OCS, and less than 1% in six studies (60%).…”
Section: Biomarkers Of Type-2 Inflammationmentioning
confidence: 96%
See 2 more Smart Citations
“…The smallest reduction of 41% (95% CI: 15, 66) was observed in a study where all patients were receiving at least 10mg of maintenance OCS daily. [18] Sputum eosinophils were reduced by 89% (95% CI: 79, 98; Figure 3), with decreases of in excess of 80% reported in eight (80%) studies. Mean sputum eosinophils were less than 3% in nine (90%) studies following OCS, and less than 1% in six studies (60%).…”
Section: Biomarkers Of Type-2 Inflammationmentioning
confidence: 96%
“…[5,6,13,16,17] Similarly, a strong statistically-significant positive association between blood eosinophils and OCS response was reported in three studies. [5,6,18] Higher baseline FeNO was also associated with a stronger OCS response in three studies [5,17,18], although one reported inconclusive results. [12] A smaller number of studies have reported a significantly larger OCS response among CS non-users (n=2) [14,15], patients with higher symptom scores (n=1) [5], and those with later onset asthma (n=1).…”
Section: Correlates Of Ocs Responsementioning
confidence: 99%
See 1 more Smart Citation
“…A systematic review and meta-analysis including 61 studies found that oral corticosteroids improved lung function and reduced asthma symptoms and markers of type 2 inflammation and that patients with increased sputum and blood eosinophils at baseline were more responsive to treatment with oral corticosteroids [ 44 ]. In a clinical study of OCS-dependent asthmatic individuals, several type-2-related biomarkers returned to baseline levels after month after treatment (0.5 mg/kg prednisolone for 7 days) [ 45 ].…”
Section: Biomarkers In Asthmamentioning
confidence: 99%
“…PD has been the most effective and safer drug for HP for a long time. It can strongly suppress several cytokines, such as IL-1, IL-6, TNF-α, and type-2 biomarker [ 3 4 ]. Further, the short course of PD does not lower the overall immunity, and hypersensitivity reactions are less common than methylprednisolone [ 5 ].…”
mentioning
confidence: 99%